PEMERIKSAAN Escherichia coli PADA DEPOT AIR MINUM ISI ULANG DIKECAMATAN KOTA KUALA SIMPANG - Eka Margaret Sinaga; Erly Sitompul; Elly Sitorus (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
The availability of clean water is decreasing along with the development of dense population growth. Many households choose Refill Drinking Water as an alternative because the price is relatively cheap. However, no one can guarantee the pathogenic bacteria contained in Refill Drinking Water. This study aims to determine the presence of Escherichia coli bacteria in refill drinking water in Kualasimpang City. This type of research is descriptive with an observational approach. The population in this study were all Refill Drinking Water Depots (DAMIU) in Kualasimpang City in 2018, totaling 21 Refill Drinking Water Depots (DAMIU). The research sample was distributed gallon water, this sample was taken from 5 Refill Drinking Depots which were selected using the Random Sampling method. The results of the study did not show the presence of Escherichia coli bacteria in refilled drinking water but only Coliform pathogenic bacteria. The quality of the water means that it is in accordance with the standards of the Minister of Health of the Republic of Indonesia No.492/MENKES/PER/IV/2010 concerning the requirements for the quality of drinking water, where drinking water must not contain bacteria in it.